LEGAL CERTAINTY ON THE STATUS OF THE INTERNAL COURT EXECUTION OBJECT GUARANTEE FIDUCIARY - Afnaini Afnaini (Sean Institute, 2023)
Hope for justice seekers regarding the provisions in the Fiduciary Law incised a bright spot when the Constitutional Court passed its 3 (three) decisions, i.e., Decision Number 18/PUU-XVII/2019, Decision Number 2/PUU-XIX/2021, And Decision Number 71/PUU-XIX/2021 decided on a judicial review case on norms relating to the execution of fiduciary guarantee objects. Issues raised in research that is How legal certainty regarding the position of the Court in the execution of fiduciary object guarantees in the Fiduciary Law. This research use type study law normative with approach legislation invitations, conceptual and cases which were then analyzed qualitatively. The study also concludes that the Constitutional Court passed the 3 (three) Decisions has provided guarantees of legal certainty for the court's position in this matter of execution of fiduciary guarantee objects in the Fiduciary Law. Assurance law on the position of the court is essential to be realized because the court as The judiciary is a legal structure that is one of them the 3 (three) elements of the legal system which largely determine the order and reform of the law to dream of. Legal certainty guarantees to achieve objective law in side justice And expediency. In the framework, implement recognition, respect, and protection of constitutional rights entrusted by the 1945 Constitution as law highest.